The effect of diet on the nutrition and production of merino ewes in the arid shrublands of Western Australia - Daly, Fiona Frances Margaret (Curtin University, 2009)
For the Arid Shrublands of Western Australia (WA) knowledge is limited on what sheep eat and how nutritious their diets are. A study was undertaken on two stations near Yalgoo (28º18’S 116º38’E) in WA, from November 2005 to December 2007. Station 1 (28º39’S 116º18’E) used a flexible rotational grazing management system (RGS), moving 3000-4000 Merino sheep every 3 – 6 weeks through a choice of 20 paddocks. Station 2 (28º18’S 116º42’E) used a flexible continuous grazing management system where small mobs (500 sheep) stayed in paddocks all year, until shearing. Two paddocks on Station 2 were chosen to represent paddocks with high (CGS-G) and low (CGS-P) feed value.A total of 300 Merino hogget (18 months old) ewes were randomly selected from the stations. One hundred and fifty sheep from each station were selected and separated into three mobs of 50 sheep by stratifying live weights. The selected sheep were allocated to either of the two paddocks on Station 2 or the single rotating mob on Station 1. Therefore there were a total of 100 sheep, 50 from each station, on each of the two paddocks on Station 2 and the one rotating mob on Station 1.Throughout the study period sheep live weights, body condition scores (BCS) and wool production were measured and related to plant photosynthetic activity (derived from Normalised Difference Vegetation Index - NDVI), and dietary energy, protein and digestibility (determined from faecal NIRS calibrations). A DNA reference data bank of some common native plant species was established and then used as a library to identify plant species in sheep faeces and thus provide information on variations in diet composition over the study period. Plant nutritional content was also measured and compared to climatic changes and sheep nutrition.Over the study period Merino ewe live weights, wool production, faecal samples and native plant leaf material were collected and analysed from each of the three management treatments (RGS, CGS-G, CGS-P). Wool production measurements included wool length, strength and fibre diameter, including position of breaks, minimum and maximum diameter along the staple of midside samples. Oven dried plant and faecal samples were ground and subsequently analysed for proximate composition. Plant samples were further analysed for mineral contents and 24 h in vitro gas production (GP) using the rumen buffer gas fermentation technique. Organic matter digestibility (OMD) and metabolisable energy (ME) content of the plants were determined using 24 h net gas production. Faecal near infrared reflectance spectroscopy (fNIRS) calibrations, developed by Curtin University of Technology and ChemCentre WA, were used to predict the nutritional attributes of sheep diets.Sheep production was found to be affected by rainfall, seasons, management and differing blood lines. In 2006, live weights, BCS and wool fibre diameter increased in response to high summer rainfall. Lower rainfall in 2007 resulted in variable, but generally less animal production with lower live weights, BCS and wool fibre diameter. Management decisions to avoid mating in 2006 on CGS; and agistment for sheep on RGS at the end of 2006 resulted in better sheep production results. Sheep originally sourced from Station 2 generally had higher live weights than sheep sourced from Station 1, suggesting a difference in bloodlines.Faecal DNA provided useful information regarding diet selection and diversity of sheep grazing on the Arid Shrublands of WA. Of the species that were DNA profiled, the sheep ate Acacia saligna, Aristida contorta, Atriplex spp., Enchylaena tomentosa, Frankenia sp., Ptilotus obovatus, Rhagodia eremaea and Scaevola spinescens in 2006 whilst in 2007; the sheep consumed A. saligna, A. contorta, Atriplex spp., Eremophila forrestii, Enneapogon caerulescens, Frankenia spp., Maireana spp., Ptilotus obovatus, Rhagodia eremaea, Solanum lasiophyllum and Stipa elegantissima. However, there were 28 amplified bands in 2006 and 51 in 2007 that did not conclusively match any of the reference plant species. This indicates that the sheep were consuming diets that contained more species than what was analysed in this study. Faecal DNA results indicated a decrease in the diversity of the diets selected by the sheep during summer, which coincided with a decrease in animal production.Native plants were found to be low in OMD and ME, but high in crude protein (CP), and variable in mineral content. Sheep were able to select diets adequate in OMD, ME and CP for maintenance requirements, and low in tannins and phenolics, although continuous drought conditions resulted in reduced production, indicating that the sheep were not getting adequate nutrition to meet their growth requirements. The use of fNIRS provided more useful information about the quality of the diet of the sheep than nutritionally profiling individual plants. NDVI was found to be related to dietary OMD and wool fibre diameter changes along the staple.Overall, the effects of management seemed to be secondary to the effects of climate on sheep production and nutrition. The statistical accuracy of results was low; however, the use of advanced technologies to explore relationships between climate, plant nutritional profiles and animal production and nutrition has provided an expansion of knowledge of sheep nutrition in the region. This extra knowledge may help land owners in the region to make more sustainable management decisions concerning livestock management and grazing pressures on native pastures.